THE IMPACT OF ARTIFICIAL INTELLIGENCE TOOLS ON EDUCATIONAL MOTIVATION AND REDUCTION OF LANGUAGE BARRIER IN TEACHING RUSSIAN AS A FOREIGN LANGUAGE (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
The article examines the psychological and pedagogical impact of AI tools (Duolingo, Quizlet, DeepL, chatbots) on educational motivation and the reduction of the language barrier (affective filter) in teaching Russian as a foreign language (RFL) to Uzbek-speaking students. Based on an experiment at School No. 5 in Jizzakh (A2 level, n=20), it is shown that AI reduces language anxiety in 78% of students, increases intrinsic and game-based motivation, and accelerates skill automation. A hybrid teaching model is proposed: AI for personalisation and psychological support, the teacher for live communication.